The mopwater files [compact disc, unabridged] - Erickson, John R., 1943- (Erickson, John R., 1943- Hank the Cowdog, 1997)
Hank the Cowdog, head of ranch security, discovers that drinking a bucket of plant food restores his energy but also gives him a serious case of mopwater poisoning.